Primary health care ‘From Alma-Ata to Astana’ - Cupertino de Barros, Fernando Passos (2022)
Funding Information: The authors are grateful for the support of the National Director of Health of Angola, Dr. Helga Freitas, and the Director of the Institute of Hygiene and Tropical Medicine at Universidade Nova de Lisboa, Professor Filomeno Fortes. They are also grateful for the participation of the Minister of Health of Angola in the opening session of the seminar.